Seasonal variation in concentration of heavy metals in tropical river sediment - Madzlan, Nur Amirah Hidayah; Suratman, Suhaimi; Mohamed, Khairul Nizam; Chuan, Ong Meng (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2023)
Heavy metal contamination has a more significant impact than microbial and organic contaminations as the elements could remain in the aqueous and particulate phases for an extended period. Setiu River, Terengganu, is one of the crucial rivers utilised as sites for aquaculture by the local communities. Generally, the concentrations of lead (Pb), zinc (Zn), copper (Cu), and arsenic (As) were influenced by human activities around river systems. Consequently, the present study investigated the seasonal concentration variations of Pb, Zn, Cu, and As in the surficial sediment of the river. The sediment samples were collected between January and July 2017, corresponding to the wet and dry seasons, from 60 different sampling locations along the river. The samples were subjected to Teflon bomb closed digestion procedures with mixed acid before the concentrations of the metals were determined with inductively coupled plasma mass spectrometry (ICP-MS). Resultantly, the mean concentrations of Pb, Zn, Cu, and As were 19.9 ± 9.89, 68.4 ± 31.8, 1.30 ± 0.66, and 3.05 ± 0.53 µg/g dry weight (wt.), respectively, in the samples gathered in the wet season (January). Alternatively, the samples collected during the dry season (July) contained 16.7 ± 15.1, 68.9 ± 48.5, 14.7 ± 16.9, and 2.46 ± 2.78 µg/g dry wt. mean concentrations of Pb, Zn, Cu, and As, respectively. The sample sediment quality was assessed based on the geoaccumulation index (Igeo). Based on the Igeo, the area was considered uncontaminated to moderately contaminated as the average values acquired were within Classes 0 and 2. Nevertheless, the pollution load index (PLI) revealed elevated concentrations of the metals, thus indicating anthropogenic sources, particularly in the aquaculture area. Accordingly, the Setiu river was assumed to be slightly polluted as the PLI values were 1.25 ± 0.34 (wet season) and 1.00 ± 1.00 (dry season).